Study on determination and removal of metallic ions from aqueous and alcoholic solutions using a new POSS adsorbent - Vieira, Eduardo G. [UNESP]; Soares, Isaac V. [UNESP]; Pires, Geovanna; Ramos, Ricardo A. V. [UNESP]; Carmo, Devaney R. do [UNESP]; Dias Filho, Newton L. [UNESP] (Elsevier B.V., 2015)
In this study, a new nanostructured organosilicate, named Octakis[(thiourea)propyl] octasilsesquioxane (POSS-Pr-THIO) was prepared, characterized and used for determination and removal of the ions Fe3+, Cr3+, V3+ and Zn2+ and compared with 3-[(thiourea) propyl] silica gel (SG-Pr-THIO). To the best of our knowledge, this study is the first that has reported the preparation of POSS-Pr-THIO and the comparison with its analogous SG-Pr-THIO for removal by batch and column experiments of toxics metals from natural waters, fuel ethanol and sugar-cane spirits. Langmuir and pseudo-second order models were the most appropriate to describe the adsorption and kinetic data respectively. Thermodynamic functions showed a feasible, spontaneous and endothermic process. The method of quantitative analysis of metal ions in natural waters, fuel ethanol and sugar-cane spirits by Flame AAS was validated using, namely, linearity, limit of detection, limit of quantification, and the relative standard deviation and accuracy. The results obtained in the flow of experiments in natural waters, fuel ethanol and sugar-cane spirit solutions, showed a recovery of nearly 100% of the metal ions adsorbed in a column packed with 1.0 g of material, using 5 mL of 1.0 M HCl solution as eluent (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Silsesquioxane; Silica; Thiourea; Preconcentration/determination